The Myth of Cultured Meat: A Review - Chriki, Sghaier; Hocquette, Jean-François (Frontiers in Nutrition, 2020)
To satisfy the increasing demand for food by the growing human population, cultured meat (also called in vitro, artificial or lab-grown meat) is presented by its advocates as a good alternative for consumers who want to be more responsible but do not wish to change their diet. In terms of technical issues, research is still required to optimize cell culture, for instance in terms of culture medium. Nevertheless, whereas we can produce muscle cells, it is almost impossible to reproduce the diversity of meats derived from various species, breeds and cuts. Although these are not yet known, we speculated on the potential health benefits and drawbacks of cultured meat. It is true that the absence of adjacent digestive organs would suggest that cultured muscle cells may be safer. On the other hand, with this high level of cell multiplication, some dysregulation is likely as happens in cancer cells. Likewise, the control of its nutritional composition is still unclear, especially for micronutrients. Regarding environmental issues, the potential advantages of cultured meat for greenhouse gas emissions are a matter of controversy, although less land will be used compared to livestock. However, more criteria need to be taken into account for a comparison with current meat production. Regarding the market share, cultured meat will have to compete with other meat substitutes, especially plant-based alternatives, with many of these already commercialized, unlike artificial meat. Consumer acceptance will be strongly influenced by the name given to this new product, since consumers tend to reject “in vitro” or “cultured” meat technology. In fact, consumers seem to dislike unnatural food. Ethically, cultured meat aims to use considerably fewer animals than conventional livestock farming, making it attractive to vegetarians and vegans. However, some animals will still have to be reared to harvest cells for the production of in vitro meat. Finally, we discussed in this review the nebulous status of cultured meat from a religious point of view. Indeed, religious authorities are still debating the question of whether in vitro meat is kosher or Halal (e.g. compliant with Jewish or Islamic dietary laws).